Pengaruh Welding Time pada Resistance Spot Welding terhadap Sifat Mekanik DIN 1.4003 - Salim, Alfi Tranggono Agus; Yusdetira, Elza Febri; Rahmawati, Ananda Nur; Wahidah, Vivi Aulia Husna; Akram, Permata Luthfiya; Saputra, Mahendra Wisnu (Jurnal Permadi : Perancangan, Manufaktur, Material dan Energi, 2025)
The process of making train sidewalls made of stainless steel using resistance spot welding (RSW) at PT INKA (Persero) experienced problems related to the quality of welding joints that were not optimal due to the mismatch between welding time, welding current, and the thickness of the material used. Therefore, it is necessary to set the right welding parameters so that the quality of the connection can be optimized and avoid failure. One of the most important parameters taken into account in the resistance spot welding (RSW) process is the welding time. This study aims to analyze the effect of welding time variations on mechanical properties, such as shear strength and hardness, of DIN 1.4003 material applied to stainless steel train sidewalls. The research was conducted using the Resistance Spot Welding method with welding time variations of 11, 15, 19, and 21 cycles. The results obtained show that the shortest welding time has the lowest shear strength and highest hardness value, and the longest welding time has the highest shear strength and lowest hardness value. The conclusion of this research is that welding time affects the mechanical properties (shear strength and hardness) of DIN 1.4003 material.